I-PD and PD controllers designed by CRA for overhead crane system - Sridokbuap, Wanlop; Nundrakwang, Songmoung; Benjanarasuth, Taworn; Ngamwiwit, Jongkol; Komine, Noriyuki (My University, 2007)
An overhead crane system controlled by an I-PD controller incorporating with PD controller is presented in this paper. The characteristic ratio assignment method is employed to design the I-PD controller and the PD controller for controlling the position of trolley and for controlling the load swing angle of the overhead crane system, respectively. Using the concept of characteristic ratio assignment method, the speed of the step response can also be increased by using a design factor k. The simulation results show that the step response can reach to the desired position without overshoot and with small load swing angle. The slightly change of the step responses when changing the parameters of the overhead crane system are also shown. The simulation results also show that when the speed of the step response is increased, the load swing angle is large related to the speed increased while the disturbance effect rejection is fast. © ICROS.
Keywords: Characteristic ratio assignment; I-PD; Overhead crane system; PD